Prototypes, Genres, and Concepts:: Travelling with Narratives - Hyvärinen, Matti (Narrative Matters, 2012)
The “narrative turn” is (too) often understood as a celebratory term indicating the growing importance and popularity of narrative studies. This article elaborates the merits of a more critical approach to the history of narrative theory. By discussing David Herman’s idea of prototypical narrativity, the article suggests that there has been a longstanding contradiction between the abstract and universal notion of narrative and the narrow and particular Proppian prototype of narrativity. The article argues that “narrative” has primarily travelled either as a concept, metaphor, or prototype rather than as a full narrative theory or method. Instead of one, unitary narrative turn, the article argues for the existence of several diverse and partly contrasting narrative turns. The recent experiential turn in narrative studies and the consequent change of the prototype of narrative gives a strong impetus for a new wave of cross-disciplinary narrative theory.